Atticism in Plutarch: a "mimesis ton arjaion" or "diglossia"? - Vela Tejada, José (Euphrosyne: Revista de filología clássica, 2019)
This paper deals with Plutarch’s work in order to establish, by means of its linguistic traits, the degree of dominance of the two linguistic-literary trends prevailing at this time: on the one hand, the Common Language, or Koine, which became the standard variety of the Greek language after an evolution starting from the Ionic-Attic High Variety; on the other, the Atticism, a reaction to this vulgarization or colloquialization that seeks the creation of a high variety for Literature, inspired by the nostalgic memory of a lost Golden Age. In short, we shall attempt to unravel whether Plutarch issues a nostalgic Atticist attempt to return to an idealized past or also evidences a relationship of diglossia rooted in the Attic dialect from the rise of Koine.